Checklist das espécies de lauxaniidae (Insecta, diptera) do estado do Mato Grosso do Sul - Silva, Vera Cristina [UNESP] (FapUNIFESP (SciELO), 2017)
Lauxaniidae is one of the largest Diptera Schizophora families, worldwide in distribution, very common in tropical areas. The family comprises about 1,550 species. Adults may be small to moderately large (2-11 mm), varied in color patterns, often with marks, spots, bands, or reticulating patterns. Larval lauxaniids are widely documented as saprophages, feeding in a diverse array of decaying plant matter, and even feeding in flower heads. Adults are fungal grazers on leaves. The Brazilian fauna of lauxaniids comprises at the moment 74 species of which 8 have been recorded from the state of Mato Grosso do Sul.
Checklist of the species of lauxaniidae (Insecta, diptera) from the state of Mato Grosso do Sul
Keywords: Biodiversity; Biota-MS program; Schizophora; Species inventory